1993
DOI: 10.1037/0022-0167.40.4.379
|View full text |Cite
|
Sign up to set email alerts
|

Congruence in client-counselor expectations for relationship and the working alliance.

Abstract: The relationship between congruence in client-counselor expectations for relationship and ratings of working alliance was examined. Participants from 25 counseling dyads completed revised versions of the Psychotherapy Expectancy Inventory (J. I. Berzins, 1971) and the Working Alliance Inventory (A. O. Horvath & L. Greenberg, 1989) after the 3rd session. Correlational analyses revealed that counselor expectations for relationship were related to counselor working alliance ratings and that client expectations fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
44
2
2

Year Published

1999
1999
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(52 citation statements)
references
References 18 publications
4
44
2
2
Order By: Relevance
“…Although evidence supports a relationship between outcome expectations and the therapeutic alliance (e.g.,Al-Darmaki and Kivilghan 1993;Joyce and Piper 1998), only limited research supports mediation of the expectations and outcomes relationship by the therapeutic alliance…”
mentioning
confidence: 95%
“…Although evidence supports a relationship between outcome expectations and the therapeutic alliance (e.g.,Al-Darmaki and Kivilghan 1993;Joyce and Piper 1998), only limited research supports mediation of the expectations and outcomes relationship by the therapeutic alliance…”
mentioning
confidence: 95%
“…Subsequent empirical investigations of the working alliance suggested that certain client (e.g., expressed hostility, quality of interpersonal relationships, relationship expectations) and therapist (e.g., training level, clinical intentions, relationship expectations) characteristics or factors may indeed impact the development of the working alliance (Al-Darmaki & Kivlighan, 1993;Dykeman & LaFleur, 1996;Kivlighan & Schmitz, 1992;Kokotovic & Tracey, 1990;Mallinckrodt & Nelson, 1991). However, uncertainty persists as to which therapist and client factors contribute to working alliance development.…”
mentioning
confidence: 99%
“…(e.g. Al-Darmaki & Kivlighan, 1993;Galassi, Crase, Martin, James, & Wallace, 1992;Kelly, 1955Kelly, /1991Kivlighan & Arthur, 2000;Rogers, 1961Rogers, /2001Tracy, 1986;Tracy & Dundon, 1988). Of particular importance is the similarity between the client's and the counsellor's/ therapist's perception of the relationship, the implication being that similarity will affect the outcome in a positive way.…”
mentioning
confidence: 95%